Aerosol‐Jet Printing of Polymer‐Sorted (6, 5) Carbon Nanotubes for Field‐Effect Transistors with High Reproducibility. (24th May 2017) - Rother, Marcel; Brohmann, Maximilian; Yang, Shuyi; Grimm, Stefan B.; Schießl, Stefan P.; Graf, Arko; Zaumseil, Jana
Abstract : Single‐walled carbon nanotubes (SWNTs) are a promising material for flexible and printed electronics. Efficient dispersion and sorting methods facilitate the production of large quantities of high‐quality semiconducting SWNT inks for direct printing. Here, the suitability of aerosol‐jet printing of polymer‐sorted (6, 5) SWNTs for top‐gate field‐effect transistors is investigated. Despite the sonication involved in the printing process, almost no impact on the quality of the SWNTs in terms of defects and length is found. Printed network transistors show reproducible device performance over extended printing periods and for different ink batches with constant printing parameters. Deposition of multiple SWNT layers to obtain thicker and optically dense films increases the effective mobility and on‐conductance, while also decreasing hysteresis. Aerosol‐jet printing of SWNTs is thus suitable for the fabrication of integrated circuits based on nanotube transistors. Abstract : Reproducible aerosol‐jet printing of semiconducting (6, 5) single‐walled carbon nanotubes is demonstrated for large numbers of field‐effect transistors with high on/off current ratios and on‐conductances at low operating voltages. Sparse and thick nanotube films can be printed with a minimum of material and good uniformity. No detrimental influence of the printing process on the transistor performance over time is observed.